1914
DOI: 10.1177/003591571400701702
|View full text |Cite
|
Sign up to set email alerts
|

Small Superficial White Rings on the Cornea

Abstract: 3 microscoped showed a profusion of round cells, but without stroma. Under the belief that it was sarcoma the eye was enucleated, and on bisecting the globe a darkly pigmented choroidal sarcoma was found lying around threefourths of the circumference of the globe. He suggested that this present case was one of sarcoma of the choroid, perforating the sclera.Small Superficial White Rings on the Cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1944
1944
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The white rings of the cornea were first described by Coats in 1912—the opacity is typically a small ring .5-1.0 mm in diameter below the epithelium or within Bowman's membrane. Although Coats initially believed the rings to be congenital and composed of calcium or lead[75], in 1969, Nevins and Elliot excised a Coat's white ring from a human eye and demonstrated that the ring contained iron deposits[76] and no calcium. Their sections of the white ring stained with Gomori's iron stain and were confirmed by electron probe x-ray microanalysis.…”
Section: Diseases Of the Corneamentioning
confidence: 99%
“…The white rings of the cornea were first described by Coats in 1912—the opacity is typically a small ring .5-1.0 mm in diameter below the epithelium or within Bowman's membrane. Although Coats initially believed the rings to be congenital and composed of calcium or lead[75], in 1969, Nevins and Elliot excised a Coat's white ring from a human eye and demonstrated that the ring contained iron deposits[76] and no calcium. Their sections of the white ring stained with Gomori's iron stain and were confirmed by electron probe x-ray microanalysis.…”
Section: Diseases Of the Corneamentioning
confidence: 99%